The structure of design and technology in the contemporary design in the interior spaces (Al-Academy, 2017)
The design of the interior spaces process the product of intellectual civilization expresses the prevailing thought, discoverers of principles and beliefs through the sheen reflects the present, and generating languages ​​graphical variety caused a different revolution in design mounting structure, and because of the complex nature of the interior spaces were and we have to be a reflection of cultural reality of being a form of cultural expression and true embodiment of scientific developments prevailing for each stage where she was born, the changes occurring in human thought and then extremism and the discrepancy tastes among individuals all communities factors have caused a change in the design structure involving modernization and down towards the contemporary technology and this is what was called search his address and the importance of modernization as a concept evolutionary as well as related concepts down to determine the importance of modern technology as an influence in building structure design, and by clarifying the behaviors that concept to enable the search to identify the research problem by asking the following: Are contemporary technology works as an influence in the formation of structure design interior spaces? The objective of the research: to identify the importance of modern technology as an influence in building structure design. The second chapter included the theoretical framework, which contained a statement of the concept of technology and contemporary concept. This statement, along with the contemporary style of relationship and modernization as well as touched upon some of the concepts put forward by the technology, and technology between the art and the path of civilization. And ensure that the third chapter research procedures in terms of methodology and the research community, and the research sample intentionality, then elected modeling analysis, and finally the fourth quarter included the findings of the search after the analysis process, and then conclusions with suggestions and recommendations.